Efficient nitrate adsorption from water by aluminum powder. Kinetic, equilibrium and influence of anion competition studies - Fakhri, Yadollah; Kakavandi, Babak; Safaei, Zahra; Asadi, Anvar; Mohsen Mohseni, Seyed; Golestanifar, Hafez (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The feasibility of aluminum powder (with particle size of 75–150 μm) for nitrate removal from aqueous solutions has been investigated. Adsorption was examined in function of initial nitrate concentration, contact time, pH and influence of other interfering anions. Maximum nitrate removal occurred at equilibrium pH of 10. The kinetics of adsorption of nitrate ions was discussed based on three kinetic models, namely: the pseudo-first order, the pseudo-second order and the intraparticle diffusion model. The experimental data fitted the pseudo-second order kinetic model very well; the rate constant was 410–4 g/ (mg·min) at the concentration of 3 NO of 100 mg/dm3. The adsorption data followed both Langmuir (R2 = 0.808) and Freundlich (R2 = 0.865) isotherms probably due to the real heterogeneous nature of the surface sites involved in the nitrate uptake. The maximum sorption capacity of aluminum powder for nitrate adsorption was found to be ca. 45.2 mg/g at room temperature. The results indicate that aluminum powder is an interesting alternative for nitrate removal from the water.
Environment Protection Engineering. Vol. 44, 2018, nr 3, s. 19-31
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma